Structural Domains within the 3′ Untranslated Region of Turnip Crinkle Virus - McCormack, John C. (American Society for Microbiology (ASM), 2008)
The genomes of positive-strand RNA viruses undergo conformational shifts that complicate efforts to equate structures with function. We have initiated a detailed analysis of secondary and tertiary elements within the 3′ end of Turnip crinkle virus (TCV) that are required for viral accumulation in vivo. MPGAfold, a massively parallel genetic algorithm, suggested the presence of five hairpins (H4a, H4b, and previously identified hairpins H4, H5, and Pr) and one H-type pseudoknot (Ψ(3)) within the 3′-terminal 194 nucleotides (nt). In vivo compensatory mutagenesis analyses confirmed the existence of H4a, H4b, Ψ(3) and a second pseudoknot (Ψ(2)) previously identified in a TCV satellite RNA. In-line structure probing of the 194-nt fragment supported the coexistence of H4, H4a, H4b, Ψ(3) and a pseudoknot that connects H5 and the 3′ end (Ψ(1)). Stepwise replacements of TCV elements with the comparable elements from Cardamine chlorotic fleck virus indicated that the complete 142-nt 3′ end, and subsets containing Ψ(3), H4a, and H4b or Ψ(3), H4a, H4b, H5, and Ψ(2), form functional domains for virus accumulation in vivo. A new 3-D molecular modeling protocol (RNA2D3D) predicted that H4a, H4b, H5, Ψ(3), and Ψ(2) are capable of simultaneous existence and bears some resemblance to a tRNA. The related Japanese iris necrotic ring virus does not have comparable domains. These results provide a framework for determining how interconnected elements participate in processes that require 3′ untranslated region sequences such as translation and replication.